2011
DOI: 10.1007/s10554-011-9853-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance assessment of left ventricular diastolic dysfunction for detecting cardiac allograft vasculopathy in recipients of heart transplants

Abstract: Cardiac allograft vasculopathy (CAV) is a major late complication in heart transplant recipients, graded based on intravascular ultrasound (IVUS), and accelerates left ventricular (LV) diastolic dysfunction. We investigated the clinical feasibility of using magnetic resonance (MR) to assess LV diastolic dysfunction noninvasively in transplant recipients. Thirty-eight asymptomatic recipients (25 men, 37.2 ± 14.9 years) underwent both IVUS and cardiac MR. Based on IVUS, we divided the individuals into 2 groups u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…ICA, invasive coronary angiography; LAD, left anterior descending artery; LCx, left circumflex artery; LM, left main artery; LV, left ventricle; LVEF, left ventricular ejection fraction; MBF, myocardial blood flow; OM, obtuse marginal; RV, right ventricle. Adapted from Bravo PE et al, 2018 (10.1093/eurheartj/ehx683) [ 87 76 ] …”
Section: Nuclear Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…ICA, invasive coronary angiography; LAD, left anterior descending artery; LCx, left circumflex artery; LM, left main artery; LV, left ventricle; LVEF, left ventricular ejection fraction; MBF, myocardial blood flow; OM, obtuse marginal; RV, right ventricle. Adapted from Bravo PE et al, 2018 (10.1093/eurheartj/ehx683) [ 87 76 ] …”
Section: Nuclear Imagingmentioning
confidence: 99%
“…First encouraging data derive from the analysis of the peak filling rate, which is an estimate of diastolic function, whose values were lower in advanced CAV rather than in earlier stages. Indeed, early diastolic strain rate impairment was successively associated to microvascular dysfunction [ 86 ], while LVEF, stroke volume and cardiac output may be found normal either in early and late stages [ 87 ]. These results might hint that diastolic dysfunction in this population might be more sensitive than indexes of systolic function for the precocious detection of CAV.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%
“…Furthermore, the CAV2/3 group had a significantly larger LV dimension than the CAV1 group. Previous studies have shown that LV function is an important prognostic factor in patients after HT, and the presence of CAV is associated with diastolic and systolic dysfunction of the LV [ 32 36 ]. Another study also showed a significant increase in LV end systolic volume and end diastolic volume in patients with moderate and severe CAV [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other than measuring myocardial perfusion, diastolic strain evaluation has also been shown to be a valuable parameter in the determination of CAV . Assessing other parameters, such as peak filling rate may allow for the evaluation of diastolic dysfunction that is associated with CAV before left ventricular systolic dysfunction and myocardial infarction or scar come to fruition . Diastolic dysfunction as assessed by MR has additionally been found to precede impairment in CFR, which is associated with CAV in asymptomatic OHT recipients .…”
Section: Diagnosismentioning
confidence: 99%